2022
DOI: 10.3390/ijerph191811814
|View full text |Cite
|
Sign up to set email alerts
|

Has the Digital Economy Reduced Carbon Emissions?: Analysis Based on Panel Data of 278 Cities in China

Abstract: China is undergoing an urbanization process at an unprecedented scale, and low-carbon urban development is of great significance to the completion of the “dual carbon goals”. At the same time, the digital economy has become an important engine for urban development, and its role in environmental improvement has become increasingly prominent. While the digital economy is booming, can it promote the low-carbon development of cities? Based on the panel data of 278 cities in China from 2011 to 2019, this paper dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 54 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…Compared with past papers, a similarity between them is that we both verify that the digital economy has a significant inhibitory effect on carbon emissions and can promote green and low-carbon development [ 51 , 52 ]. There are also studies contrary to the findings of this paper, in which it was shown that the digital economy can reduce carbon emissions up to a certain range and increase them beyond that [ 53 ].…”
Section: Discussionmentioning
confidence: 74%
“…Compared with past papers, a similarity between them is that we both verify that the digital economy has a significant inhibitory effect on carbon emissions and can promote green and low-carbon development [ 51 , 52 ]. There are also studies contrary to the findings of this paper, in which it was shown that the digital economy can reduce carbon emissions up to a certain range and increase them beyond that [ 53 ].…”
Section: Discussionmentioning
confidence: 74%
“…As an essential part of economic development, the digital economy not only provides new opportunities for economic growth but also plays a vital role in carbon peaking and carbon neutrality goals. With the development of the economy, more and more cities have achieved the absolute decoupling of economic growth with carbon emissions and achieved the transition to green and low-carbon development [ 17 ]. A digital economy can promote carbon emission reduction by enhancing innovation capacity, alleviating financing constraints [ 18 ], promoting industrial structure upgrading [ 19 ], and increasing investment in R&D [ 20 ], etc.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…(4) The super-efficient SBM model was adopted to recalculate the urban carbon emission efficiency. (5) Drawing on existing research [ 62 ], an index system was used to measure the level of big data construction. (6) The carbon emission performance measured by carbon emission intensity (carbon emissions per unit GDP) was used as the explained variable for robustness tests.…”
Section: Empirical Designmentioning
confidence: 99%